Developing glycoproteomics reveals the role of posttranslational glycosylation in the physiological and pathological processes of male reproduction - Qingyuan Cheng; Mengqi Luo; Zihe Xu; Fuping Li; Yong Zhang (iMetaOmics)
Abstract Glycosylation plays a pivotal role in the physiological and pathological processes of male reproduction. It impacts thousands of proteins and is actively ongoing through all stages of reproduction, including spermatogenesis, maturation, capacitation, and fertilization. However, our grasp on glycosylation within male reproductive processes remains limited, largely due to the technical hurdles. Recent advancements have seen the mapping of the glycoproteome of human semen, utilizing cutting‐edge glycoproteomic technologies. This breakthrough lays the groundwork for in‐depth research into the influence of glycosylation on male reproductive system and related disorders. Nevertheless, the field faces numerous challenges that necessitate further advancements in glycoproteomic methodologies. In this analysis, we evaluated the potential applications of advanced glycoproteomic techniques in the study of male reproduction and summarized the detailed profiling of the human semen glycome and glycoproteome. Our current understanding of glycosylation's role within the male reproductive system alongside recent progress in glycoproteomics may equip biologists with a comprehensive insight. Furthermore, this analysis brought together findings on abnormal glycosylation and its link to male reproductive disorders in the view of glycomics and glycoproteomics. It can facilitate the clinical application of glyco‐related biomarkers and targets in the treatment of infertility.